A GOVERNMENTAL AGENCY'S PROGRAM FOR DEVELOPING ITS PROFESSIONAL ACCOUNTANTS. - Campfield, William L. (The Accounting Review, 1962)
Abstract During the past decade, the Federal Government has made considerable progress in improving the management of its financial affairs. A substantial part of this progress is attributable to the professional caliber of the accounting and auditing personnel who have aided and counseled Federal executives during this decade of improvement. This paper has presented the highlights of the program of one governmental agency to further the professional training and development of its auditor staff. This Agency, the U. S. Army Audit Agency, has developed and strengthened a planned, purposeful program for developing personnel of a high professional stature. In the years ahead, it is expected that the Agency's training and development methods and programs will continually be sharpened and will be rightfully recognized by the accounting profession as a significant contribution to the totality of excellence that is the hallmark of the profession. The progress achieved by government internal auditors during the past decade attests to the fact that professional auditing has come of age as an instrument for furthering the cause of good management in Government. It is not too far fetched to suggest that the general approach and training program for auditors such as that followed by the U. S. Army Audit Agency might be useful to other organizations, public or private, in developing their staff.